2019
DOI: 10.1155/2019/9035396
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Constitutive Model of Thermal Damage for Deep Rock considering Initial Compaction Stage and Residual Strength

Abstract: From the theory of damage mechanics, based on the Hoek-Brown strength criterion and Weibull distribution law of rock microelement strength, a statistical constitutive model of rock thermal damage is established by using equivalent strain hypothesis, and the theoretical model is modified by considering the compression coefficient and residual strength correction coefficient. The rationality of the modified model is verified by experimental data. The results show that the stress-strain curves of rock can be divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…Suppose that the macroscopic rock is made up of N meso-elements which are continuous with each other. As the stress level increases, these meso-elements are destroyed, and their number N d increases, the damage variable D can be expressed as [ 18 20 ]: with substituting Eq ( 9 ) into Eq ( 10 ), the damage variable with maximum entropy can be expressed as …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Suppose that the macroscopic rock is made up of N meso-elements which are continuous with each other. As the stress level increases, these meso-elements are destroyed, and their number N d increases, the damage variable D can be expressed as [ 18 20 ]: with substituting Eq ( 9 ) into Eq ( 10 ), the damage variable with maximum entropy can be expressed as …”
Section: Methodsmentioning
confidence: 99%
“…The mechanical properties of rock are directly affected by the stress level of the internal structure, and this approach is just in line with this point. However, the residual strength, that is, the strength of the softened area after the peak value of the rock, is difficult to be fully modeled, Xu [ 17 ] and Zhu [ 18 ] improved the statistical damage mode by introducing a damage correction factor, which only belonged to a mathematical concept and did not involve the mesoscopic model itself. In other similar studies, the development of rock damage is viewed as a slow process of damage accumulation, and the undamaged area would gradually change into the damaged area which still bear the load rather than become a hollow area [ 19 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Krajcinovic and Silva [ 14 ] were the first to combine the continuous-strength damage theory with statistics to study the mechanical behavior of rocks. Subsequently, some improved statistical damage models were constantly proposed with the statistical microscopic damage mechanics [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. The key to characterizing the damage evolution in statistical damage theory is establishing a probability density function of the micro-elements’ strength.…”
Section: Introductionmentioning
confidence: 99%
“…By studying the static and dynamic damage characteristics of deep rocks in high temperature environment, it was seen that the thermal damage delayed the rock crack process and weaken the brittleness 14 16 , and it was also found that static and dynamic compressive strength, tensile strength and shear strength decreased with the increasing temperature 17 – 20 . Part of scholars established the constitutive model of thermal damage in deep rocks based on damage mechanics and the influence of high temperature on the rock, which improve the accuracy of predicting the rock failure in the high-temperature condition 21 – 23 . The scholars in field of rock mechanics carried out exploratory studies on the damage failure mechanism of deep rocks affected by cool and hot water.…”
Section: Introductionmentioning
confidence: 99%